Development of a Concentration Cell Potentiometric Method for Fe2+ and Fe3+ Speciation - Izzati Izzati; Suheryanto Suheryanto; Poedji Loekitowati Hariani (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2023)
The speciation of Fe2+ and Fe3+ iron ions using the concentration cell potentiometric method has been developed. The determination and speciation of metals that have been used include potentiometry using comparison electrodes, selective ion electrodes, and voltammetry. The concentration cell potentiometric method has the advantages of simple equipment, the use of common metal electrodes, high selectivity, and relatively low detection limits. The method validation results for Fe2+ and Fe3+ ion speciation were LOD: Fe2+ 0.22 mg/L Fe3+ 0.29, LOQ: Fe2+ 0,92 mg/L ; Fe3+ 0,01 mg/L, precision (1.17%; 1.2%) and accuracy (95.57%; 93.15%) based on CV Horwtz.Â  This method has been well applied for Fe2+ and Fe3+ speciation in natural water samples. The concentrations of Fe2+ and Fe3+ species in Sekanak river water were (1.88 mg/L; 2.07 mg/L). Concentration of Fe2+ and Fe3+ species in well water samples (0.5 mg/L; 1.32 mg/L).